Failure at Fidenae: Understanding the site of the largest structural disaster of the Roman world. (September 2018) - Napolitano, Rebecca; Monce, Michael
Abstract: In A.D. 27 the largest structural disaster of the Roman world occurred when the amphitheater at Fidenae collapsed involving what one source reported to be 50, 000 people. A 3D digital reconstruction of the amphitheater was produced from textual, architectural, archaeological, and engineering analysis. Primary literary sources, such as Roman authors Tacitus and Suetonius, examined in conjunction with proximal archaeological evidence allowed for the most probable seating capacity and the scale of the amphitheater to be determined; architectural evidence of other wooden structures found on Trajan's Column allowed for a most probable projection of a three-dimensional model to be created utilizing AutoCAD. The failure of the amphitheater at Fidenae stands in the middle of an important period for the development of large-scale Roman infrastructure; through understanding failed designs such as this one, more light can be shed on the progression of technological advances and development of engineering practices in ancient Rome. Graphical abstract: Highlights: Failed engineering projects illustrate the level of building knowledge at a time. Engineering analysis can help to rediscover the possibilities of the past. Digital reconstructions are a non-unique process which promote future inquiry.